Diglossia, Reproach, and Celestial Time: Indigenous Astronomy as a Framework for Understanding Ethiopian Verbal Character - Belay Sitotaw Goshu; Arifulhak Aceh; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2026)
Ethiopian diglossia (Ge‛ez/Amharic) has long been described as a functional hierarchy between liturgical and everyday language. However, this classical model does not explain why Amharic and Oromo speakers exhibit both elaborate politeness (yilugnta) and forceful direct reproach among intimates a paradox that challenges universal politeness frameworks. This study investigates how indigenous astronomical knowledge regulates the speech act of Mekdes (loyal reproach) and proposes an integrated model of Ethiopian verbal character that extends diglossia theory beyond the linguistic domain. A mixed methods ethnographic design was employed, comprising structured interviews with 250 participants (145 male, 105 female) across Addis Ababa, Adama, Debre Berhan, Dire Dawa, and Hawasa; 30 hours of naturalistic audio recorded interactions; elicitation of 50 star related proverbs; and extended participant observation during planting seasons and ritual festivals. Mekdes is a face building act characterised by raised volume, slower tempo, direct pronouns, and forward lean—features that signal belonging rather than threat. The heliacal rising of Bakkalcha (Pleiades) marks the transition from polite caution to permissible reproach. Star names (Saddu: unity; Gulshān: revelation; Gabbiya: accountability) encode moral pedagogy. Celestial diglossia a functional split between priestly and farmer level astronomical registers parallels linguistic diglossia and authorises Mekdes through distinct channels. Ethiopian verbal character is not contradictory but bidirectionally regulated by celestial time. The stars provide a moral clock that tells speakers when a relationship has ripened from stranger hood to intimacy, thereby transforming reproach from face threat into face gift. Educational curricula, intercultural training, and language policy should integrate indigenous astronomical knowledge as essential to communicative competence in Ethiopian highland communities.